Design analysis of laminated composite ladder chassis frame of light truck - Abdullah, Kassim Abdulrahman; Rosli, Mohd Zaimi (IIUM Press, 2011)
The truck chassis is a major component in a vehicle system. In the design process of the vehicle, the chassis frame is often subjected to refiiement in order to develop vehicles with reduced cost and weight [I]. The application of FEA is used to reduce component complexity, weight and subsequently cost.